INVESTMENT PORTFOLIO SET-UP IN TERMS OF JSC NC "KAZAKHSTAN TEMIR ZHOLY" - Nesipbekov, Ye. N.; Appakova, G.N. (Academic Journal of Physical and Chemical Sciences, 2018)
. Present article is aimed to analyze the process of investment portfolio set-up in terms of Joint Stock Company “National Company Kazakhstan Temir Zholy” (JSC NC KTZh). The following research methods were used: the unity of historical and logical, scientific analysis and synthesis, statistical method. The factors impacting the investment policy of JSC NC KTZh were identified and systematized in course of study. The ongoing investment policy of the company has been assessed and recommendations have been issued on the investment portfolio set-up and management. Finally, the authors concluded that, there is still a number of problems to the portfolio compliance to the actual strategic demands despite the theoretically correct strategy of actions in respect to the company's investment portfolio. The results and proposals obtained during the study may be used to improve the investment policy of JSC NC KTZh.